2014
DOI: 10.1021/ol501730p
|View full text |Cite
|
Sign up to set email alerts
|

Carboxybenzyl Group as an O-Nucleophile in the C–H Allylic Oxidation: Total Synthesis of (−)-Castanospermine

Abstract: The first palladium-mediated C-H allylic oxidation with a Cbz group acting as an O-nucleophile is reported. It was found that this transformation is promoted by rare-earth metal triflates: Yb(OTf)(3) or Sc(OTf)(3). A possible catalytic cycle is proposed. This reaction was applied in the synthesis of a d-xylose derived oxazolidinon, a versatile intermediate used further in the stereoselective synthesis of unnatural (-)-castanospermine. Cyclization of the key intermediate with PhSeBr afforded the desired bicycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…25 Fortunately, upon screening a variety of additives and varying the catalyst and oxidant loadings (see Supporting Information), we found that the addition of superstoichiometric quantities of water to the reaction mixture was crucial for obtaining reproducibly good yields of lactone 26 . 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…25 Fortunately, upon screening a variety of additives and varying the catalyst and oxidant loadings (see Supporting Information), we found that the addition of superstoichiometric quantities of water to the reaction mixture was crucial for obtaining reproducibly good yields of lactone 26 . 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…10 After methanolysis, which afforded aminoalcohol 2, the N-acryloyl derivative 3a was obtained, along with considerable amounts (26%) of diacryloyl derivative 3b as a by-product. Subsequent ring-closing meta thesis (Scheme 3) of 3a with Grubbs-II cat.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, during the total synthesis of a naturally occurring iminosugar, castanospermine, a palladium-catalyzed intramolecular C−H allylic oxidation with a piperidinyl Ncarbamate (as an O-nucleophile) yielded an oxazolidinonefused piperidine derivative (Scheme 130). 163 It was found that reaction was promoted by a catalytic amount of Yb(OTf) 3 . The presence of a Lewis acid was crucial; without it, only trace amounts of product were isolated.…”
Section: Oxazolo[34-a]pyridinementioning
confidence: 99%